Resilience or decline? Insights from long-term sap flow and wood anatomy monitoring in fire-damaged Pinus pinaster Aiton forest - Niccoli, Francesco; Kabala, Jerzy Piotr; Fargnoli, Lorenza; Battipaglia, Giovanna (Frontiers in Ecology and Evolution, 2025)
Wildfires represent a major disturbance in Mediterranean forests, often triggering long-term functional decline in surviving trees. Understanding the hydraulic and eco-physiological trend of fire-affected stands is essential to assess whether trees are on a recovery path or progressing toward irreversible decline. In this study, we combined four years of continuous sap flow monitoring with wood anatomical analyses and satellite observations in a Mediterranean pine forest severely affected by fire. Continuous measurements in burned and control trees revealed contrasting transpiration strategies and progressive divergent pattern of hydraulic performance under recurrent drought conditions. Burned trees initially increased transpiration as a compensatory response but gradually exhibited signs of functional impairment, including reduced hydraulic efficiency, altered xylem traits, and limited canopy recovery. Further, remote sensing highlighted persistent canopy degradation and the spread of invasive vegetation, exacerbating water competition and accelerating decline. Control trees, by contrast, maintained a conservative water-use strategy and showed a greater capacity to exploit favorable climatic periods. These findings highlight the vulnerability of fire-damaged forest stands to eco-physiological decline, with potential implications for delayed mortality. The integration of long-term sap flow, wood anatomy, and satellite monitoring emerges as a powerful approach for detecting early-warning signals of resilience loss and informing post-fire forest management in drought-prone ecosystems.